(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This in the article artistic image individual author of the tools style in formation place and importance literary criticism theoretical and comparative approaches based on analysis In the study metaphor, epithet, simile, symbol, irony similar figurative of tools author worldview, aesthetics views and artistic his/her thinking in expression functional opportunities will be illuminated. Artistic texts analysis based on figurative tools the author’s individual creative style determinant main poetic from mechanisms one that scientific in terms of is based on. Research results artistic image tools through author of style aesthetic, semantic and pragmatic aspects formation shows. Article stylistics, literature theory and comparative literary studies in the fields scientific research for theoretical-methodological importance has.